A stalagmite test of North Atlantic SST and Iberian hydroclimate linkages over the last two glacial cycles - R. F. Denniston; A. N. Houts; Y. Asmerom; A. D. Wanamaker Jr.; J. A. Haws; V. J. Polyak; D. L. Thatcher; S. Altan-Ochir; A. C. Borowske; S. F. M. Breitenbach; C. C. Ummenhofer; F. T. Regala; et al. (Climate of the Past, 2018)
Close coupling of Iberian hydroclimate and North Atlantic sea surface temperature (SST) during recent glacial periods has been identified through the analysis of marine sediment and pollen grains co-deposited on the Portuguese continental margin. While offering precisely correlatable records, these time series have lacked a directly dated, site-specific record of continental Iberian climate spanning multiple glacial cycles as a point of comparison. Here we present a high-resolution, multi-proxy (growth dynamics and δ13C, δ18O, and δ234U values) composite stalagmite record of hydroclimate from two caves in western Portugal across the majority of the last two glacial cycles (∼220 ka). At orbital and millennial scales, stalagmite-based proxies for hydroclimate proxies covaried with SST, with elevated δ13C, δ18O, and δ234U values and/or growth hiatuses indicating reduced effective moisture coincident with periods of lowered SST during major ice-rafted debris events, in agreement with changes in palynological reconstructions of continental climate. While in many cases the Portuguese stalagmite record can be scaled to SST, in some intervals the magnitudes of stalagmite isotopic shifts, and possibly hydroclimate, appear to have been somewhat decoupled from SST.